2024
DOI: 10.3390/horticulturae10030215
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Light Intensity and Photoperiod on Morphological Development and Photosynthetic Characteristics of Coriander

Fang Wang,
Qi Gao,
Guangsi Ji
et al.

Abstract: Coriander (Coriandrum sativum L.) is prized for its aroma and medicinal properties and is extensively employed in various cuisines. Light intensity and photoperiod greatly impact its phenological development. The application of light-emitting diodes (LEDs) in facility cultivation systems enables precise control of lighting conditions, leading to enhanced energy efficiency in coriander cultivation. This study investigated three levels of light intensity (133, 200, and 400 μmol·m−2·s−1) and three photoperiods (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…As can be seen, the linalool content varied from 65.3 to 80.5%, and it was noticed that higher temperature, precipitation, and insolation lead to higher levels of linalool. There are reports that climatic factors have an effect on the quantity of essential oil and dry matter yield of coriander [62], as well as development and morphological characteristics [63]. However, previous results showed that coriander has favorable growth conditions in Serbia [64].…”
Section: Discussionmentioning
confidence: 91%
“…As can be seen, the linalool content varied from 65.3 to 80.5%, and it was noticed that higher temperature, precipitation, and insolation lead to higher levels of linalool. There are reports that climatic factors have an effect on the quantity of essential oil and dry matter yield of coriander [62], as well as development and morphological characteristics [63]. However, previous results showed that coriander has favorable growth conditions in Serbia [64].…”
Section: Discussionmentioning
confidence: 91%